Profile of students’ actual and potential competences on Aliphatic Bifunctional Organic compounds topic using RADEC model - Hayati, Nurlaila; Kadarohman, Asep; Sopandi, Wahyu; Pratiwi, Amelinda; Martoprawiro, Muhamad A. (AIP conference proceedings, 2023)
Aliphatic bifunctional organic compounds are complex topics of organic chemistry because they require reasoning on the structures, reactions, and interactions between functional groups. This study aims to describe the profile of the actual and potential competencies of students in the Structure and Reactivity of Aliphatic Bifunctional Organic Chemistry Course using the application of the Read, Answer, Discussion, Explain, Create (RADEC) model. The subject in this study consist of 37 students of the Chemistry Education Program and 33 students of the Chemistry Program at a university in Bandung. Course activities occurred via Zoom. Most components of the lecture were delivered asynchronously through the course learning management system. Students’ actual and potential competencies were assessed using pre-test and post-test through Quizizz. Data analysis used descriptive analysis and n-gain. It was found that the mean score of students’ potential competence was higher than the mean score of students’ actual competence and the n-gain score was in the medium category. The highest improvement of students’ potential competence from their actual competence was in the introduction of aliphatic bifunctional organic compounds topic for Chemistry Education Program students and the diene and diol reaction topic for Chemistry Program students, while the lowest improvement was in the retrosynthesis topic. These findings indicate that RADEC model has the potential to improve students’ actual and potential competencies.